Analysis of the Influence of Instagram Social Media @pelagaecopark on Tourists’ Visiting Interest at Pelaga Eco Park Bali - Komang Trigita Juliastari (International Journal of Entrepreneurship and Tourism, 2025)
This research was conducted at Pelaga Eco Park Bali regarding the influence of the Instagram social network on visiting intentions. Social networks play an important role in connecting the world between one person and another, Instagram is a social network based on sharing photos and videos, many companies use Instagram as an advertising tool to share photos or videos about the beauty of destinations and tourist attractions. activities in these places. The aim according to Effendi in (Hassan, 2022) is that messages conveyed through content can influence the communicator or recipient of the message, so that it can cause changes in behavior. Therefore, researchers want to test whether social media, in this case Instagram, influences tourists' interest in visiting. The results of this research aim to test and explain the influence of the Instagram social network on the interest in visiting followers of the @pelagaecopark account. This research was conducted at the Pelaga Ecological Park tourist location with a research sample of 100 followers using saturated sampling techniques. All answer results obtained by distributing questionnaires are used and processed using a simple linear regression analysis system which also uses hypothesis testing. This research shows that (1) Testing hypothesis 1 shows the results that the social network Instagram (X1) has a significant influence on intention to visit (Y.). These results are based on the Instagram social media regression coefficient (bX) of 0.662 and TStat = 8.544 at a significance level of 0.00 (p < 0.05), which shows positive results so that the hypothesis can be accepted. The implication and conclusion of this test is that the better the Pelaga Eco Park Instagram social media, the more interest in visiting it will be. The influence of the social network Instagram is 39.3%. This can be seen from the FIT model above.